Development and Application of a Fully Automated Chemiluminescence Enzyme Immunoassay for the Detection of Antibodies Against Porcine Circovirus 3 Cap - Lei Wang; Duan Li; Daoping Zeng; Xiaomin Wang; Yanlin Liu; Guoliang Peng; Zheng Xu; Changxu Song (Viruses)
Porcine circovirus 3 (PCV3) is a small non-enveloped circovirus associated with porcine dermatitis and nephropathy syndrome (PDNS). It has occurred worldwide and poses a serious threat to the pig industry. However, there is no commercially available vaccine. PCV3 capsid protein (Cap) is an ideal antigen candidate for serodiagnosis. Here, a novel fully automated chemiluminescence enzyme immunoassay (CLEIA) was developed to detect antibodies (Abs) to Cap in porcine serum. Recombinant PCV3 Cap, self-assembled into virus-like particles (VLPs), was produced using baculovirus and coupled to magnetic particles (Cap-MPs) as carriers. Combined with an alkaline phosphatase (AP)–adamantane (AMPPD) system, Cap-Abs can be rapidly measured on a fully automated chemiluminescence analyzer. Under optimal conditions, a cut-off value of 31,508 was determined, with a diagnostic sensitivity of 96.8% and specificity of 97.3%. No cross-reactivity was observed with PCV1 and PCV2 and other common porcine pathogens, and both intra-assay and inter-assay coefficients were less than 5% and 10%, respectively. Prepared Cap-MPs can be stored at 4 °C for more than 6 months. Importantly, this CLEIA had a good agreement of 95.19% with the commercially available kit, demonstrating excellent analytical sensitivity and significantly reduced operating time and labor. A serological survey was then conducted, and showed that PCV3 continues to spread widely in South China. In conclusion, our CLEIA provides time and labor-saving, and a reliable tool for PCV3 epidemiological surveillance.